The Association of Gut Microbiota With Idiopathic Central Precocious Puberty in Girls - Dong, Guoqing; Zhang, Jiyong; Yang, Zhenyu; Feng, Xin; Li, Jianxu; Li, Dongfang; Huang, Miao; Li, Yinhu; Qiu, Minghui; Lu, Xiyan; Liu, Peihui; Zeng, Yongmei; et al. (Frontiers in Endocrinology, 2020)
Idiopathic central precocious puberty (ICPP) is a common disease in preadolescence girls, and its pathogenesis remains to be uncovered. A variety of studies highlighted the association of the gut microbiota (GM) with endocrine diseases, such as obesity, which is a common complication in ICPP. However, the relationship between GM and ICPP remains unexplored. Feces samples were collected from 25 girls with ICPP (ICPP group) and 23 healthy girls (Control group). We applied 16S rDNA sequencing to compare the GM between two groups. The ICPP group had higher GM diversity and was enriched for several GM species, including Ruminococcus gnavus, Ruminococcus callidus, Ruminococcus bromii, Roseburia inulinivorans, Coprococcus eutactus, Clostridium leptum, and Clostridium lactatifermentans, which are known to be correlated with obesity and are related with the production of short-chain fatty acids. Additionally, 36 candidate GM biomarkers for patients with ICPP screening were identified with high accuracy (AUC = 0.95, 95% CI 0.88 to 1). We observed that the GM of the ICPP group was enriched for the microbial functions of cell motility, signal transduction, and environmental adaptation. Positive correlations were also detected between Fusobacterium and follicle-stimulating hormone, and Gemmiger and luteinizing hormone. This study documents the relationships between GM and ICPP, and provides an extensive insight into ICPP diagnosis as well as prevention.